Enhancing drought tolerance in cauliflower (Brassica oleracea var. botrytis) by targeting LFY transcription factor modulation via the ethylene precursor, ACCA: an innovative computational approach - Debnath, Sandip; Elgorban, Abdallah M.; Bahkali, Ali H.; Eswaramoorthy, Rajalakshmanan; Verma, Meenakshi; Syed, Asad; Subramaniyan, Vetriselvan; Kamaraj, Chinnaperumal; Wong, Ling Shing; Kumarasamy, Vinoth (Frontiers in Plant Science, 2024)
Background: Brassica oleracea var. botrytis is an annual or biennial herbaceous vegetable plant in the Brassicaceae family notable for its edible blossom head. A lot of effort has gone into finding defense-associated proteins in order to better understand how Cauliflower and pathogens interact.Endophytes are organisms that live within the host plant and reproduce. Endophytes are bacteria and fungi that reside in plant tissues and can either help or harm the plant. Several species have aided molecular biologists and plant biotechnologists in various ways. Water is essential for a healthy cauliflower bloom. When the weather is hot, this plant dries up, and nitrogen scarcity can be detrimental to cauliflower growth.Objective: The study sought to discern Plant Growth Promoting (PGP) compounds that can amplify drought resilience and boost productivity in cauliflower.Methods: Investigations were centered on endophytes, microorganisms existing within plant tissues. The dual role of beneficial and detrimental Agrobacterial bacteria was scrutinized, particularly emphasizing the ethylene precursor compound, 1-amino-cyclopropane-1-carboxylic acid (ACCA).Results: ACCA possessed salient PGP traits, particularly demonstrating a pronounced enhancement of drought resistance in cauliflower plants. Specifically, during the pivotal marketable curd maturity phase, which necessitates defense against various threats, ACCA showcased a binding energy of -8.74 kcal/mol.ACCA holds significant promise in agriculture, with its potential to boost drought resistance and cauliflower yield. This could be particularly impactful for regions grappling with high temperatures and possible nitrogen shortages. Future research should explore ACCA's performance under diverse environmental settings and its applicability in other crops.